MODEL ON NEW CUSTOMER PURCHASE DECISION TOWARD OF PRODUCT QUALITY, LOCATION AND PROMOTION IN ELECTRIC CIGARETTE AT WEST JAKARTA - Fahlevi, Muhammad Adhlir (Universitas Mercu Buana, 2020)
This research is to find out the Model On New Customer Purchase Decision Toward of Product Quality, Location and Promotion In Electric Cigarette At West Jakarta. The subjects in this study were new consumers of electric cigarettes who made purchasing decisions at 54 Vape Store Tanjung Duren. The sample used in this study was 170 respondents. The sampling technique uses purposive sampling. By using a quantitative descriptive approach. Analysis of the data used is statistical analysis in the form of SEM-PLS. The results of this study indicate that Product Quality has a significant positive effect on Purchasing Decisions. Location has a significant positive effect on Purchasing Decisions and Promotion has a positive and not significant effect on Purchasing DecisionsÂ Keywords: Product Quality, Location, Promotion, Purchase Decision, 54 Vape Store